2021
DOI: 10.1007/s11606-021-06753-1
|View full text |Cite
|
Sign up to set email alerts
|

How Do Patients Want Us to Use the Computer During Medical Encounters?—A Discrete Choice Experiment Study

Abstract: Background Primary care physicians (PCPs) now widely use electronic health records (EHRs) during medical encounters. Experts in clinical communication issued recommendations for a patient-centered use of EHRs. However, they have never been validated by patients themselves. Objective To explore patients’ preferences regarding physicians’ EHR-related behaviors. Design Discrete choice experiment study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…11 Patients are generally interested in knowing what a doctor is doing on the computer and appreciate screen sharing. 10,12,13 Sharing the computer screen has been reported to increase collaborative decision making and trust. 14 When it comes to information seeking, optimising the physical layout of the consultation room to facilitate patient interaction with the computer can allow patients to engage with the process and have greater ownership over the information found.…”
Section: Tip 1: Set Up the Consultation Space To Facilitate Informati...mentioning
confidence: 99%
See 2 more Smart Citations
“…11 Patients are generally interested in knowing what a doctor is doing on the computer and appreciate screen sharing. 10,12,13 Sharing the computer screen has been reported to increase collaborative decision making and trust. 14 When it comes to information seeking, optimising the physical layout of the consultation room to facilitate patient interaction with the computer can allow patients to engage with the process and have greater ownership over the information found.…”
Section: Tip 1: Set Up the Consultation Space To Facilitate Informati...mentioning
confidence: 99%
“…10 A doctor using a computer in the consultation room without adequate care can lead to clinician distraction, amplification of poor communication styles and loss of rapport. 13 Patients request that prior to accessing information a doctor must first 'earn the right' to turn to a resource. This 'right' is earned through assessing the patient thoroughly and focusing attention actively before seeking information.…”
Section: Tip 2: Understand the Footing Of The Consultationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, physicians were in charge of the consultation flow by trying to involve the patients in the conversation while working on computers [ 23 ]. Furthermore, another study explored patients’ opinions regarding physicians’ interaction with the EHR by involving patients in watching videos depicting EHR-related activities and asking them about their thoughts on the matter [ 24 ]. The study found that most patients preferred physicians who talk and look at them while typing.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing administrative burdens by implementing NLP derived dictation tools would aid a long desired return to patient centred consultations 56. Furthermore, documenting in electronic health records was found to take up more than half of a general practitioner’s workday; many feel these time constraints impede provision of holistic care 5.…”
mentioning
confidence: 99%